Shortleaf Pine (Pinus echinata): Management Challenges, Knowledge Gaps, and Opportunities for an Unsung Species - Benjamin O. Knapp; Jacob Fraser; Joanne Baggs; Vikram E. Chhatre; David Clabo; Connor D. Crouch; Daniel C. Dey; Shaik M. Hossain; Steven B. Jack; John M. Kabrick; Kathryn R. Kidd; Steven McNulty; et al. (Journal of Forestry, 2026)
Shortleaf pine has the broadest range of the southern pine species, occurring in 22 states and extending north into New Jersey, Pennsylvania, and New York (Staten Island). Shortleaf pine has been understudied compared to loblolly pine and longleaf pine, typically favored for timber production and conservation value, respectively. The extensive range of shortleaf pine contributes to a high degree of variability within and among its ecosystems and contributes to the need to understand regional context in considering its ecology and management. The goal of this paper is to review and synthesize the state-of-knowledge on shortleaf pine ecosystems, emphasizing the importance of variation across its range in identifying management challenges and opportunities. We discuss the variation in growing conditions that occur across the geographic range, shortleaf pine natural community groups, and contemporary shortleaf pine forest types that occur on the landscape. We provide a review of the state-of-knowledge for topics related to shortleaf pine management, including its fire ecology, genetic considerations, economics, and others. Finally, we synthesize these into key considerations and highlight regionally specific management challenges and opportunities.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparison of two processing techniques on the sperm quality of semen contaminated with urine - Mariah M. Pearson; Camilo Hernández-Avilés; Sheila G. Spacek; Anne M.N. Beckham; Dale E. Kelley; Luisa Ramírez-Agámez; Katrina A. LaCaze; Dickson D. Varner; Charles C. Love (Theriogenology, 2024)

Pile burning after conifer removal from aspen stands affects tree mortality, regeneration, and understory recovery - John-Pascal Berrill; Christa M. Dagley; Yoon G. Kim; J. Morgan Varner (Forest Ecology and Management, 2024)

Herbaceous vegetation responses to experimental fire in savannas and forests depend on biome and climate - Zachary J. Gold; Adam F. A. Pellegrini; Tyler K. Refsland; Romina J. Andrioli; Marlin L. Bowles; Dale G. Brockway; Neil Burrows; Augusto C. Franco; Steve W. Hallgren; Sarah E. Hobbie; William A. Hoffmann; Kevin P. Kirkman; et al. (Ecology Letters, 2023)
Fire–vegetation feedbacks potentially maintain global savanna and forest distributions. Accordingly, vegetation in savanna and forest ecosystems should have differential responses to fire, but fire response data for herbaceous vegetation have yet to be synthesized across biomes. Here, we examined herbaceous vegetation responses to experimental fire at 30 sites spanning four continents. Across a variety of metrics, herbaceous vegetation increased in abundance where fire was applied, with larger responses to fire in wetter and in cooler and/or less seasonal systems. Compared to forests, savannas were associated with a 4.8 (±0.4) times larger difference in herbaceous vegetation abundance for burned versus unburned plots. In particular, grass cover decreased with fire exclusion in savannas, largely via decreases in C 4 grass cover, whereas changes in fire frequency had a relatively weak effect on grass cover in forests. These differential responses underscore the importance of fire for maintaining the vegetation structure of savannas and forests.

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Nutrients Alter Methane Production and Oxidation in a Thawing Permafrost Mire - N. Niloufar Kashi; Erik A. Hobbie; Ruth K. Varner; Adam S. Wymore; Jessica G. Ernakovich; Reiner Giesler (Ecosystems, 2023)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Fires without tanoak: the effects of a non-native disease on future community flammability - J. Morgan Varner; Howard G. Kuljian; Jesse K. Kreye (Biological Invasions, 2017)

Endogenous circadian regulation of carbon dioxide exchange in terrestrial ecosystems - Víctor Resco de Dios; Michael L. Goulden; Kiona Ogle; Andrew D. Richardson; David Y. Hollinger; Eric A. Davidson; Josu G. Alday; Greg A. Barron‐Gafford; Arnaud Carrara; Andrew S. Kowalski; Walt C. Oechel; Borja R. Reverter; et al. (Global Change Biology, 2012)
It is often assumed that daytime patterns of ecosystem carbon assimilation are mostly driven by direct physiological responses to exogenous environmental cues. Under limited environmental variability, little variation in carbon assimilation should thus be expected unless endogenous plant controls on carbon assimilation, which regulate photosynthesis in time, are active. We evaluated this assumption with eddy flux data, and we selected periods when net ecosystem exchange ( NEE ) was decoupled from environmental variability in seven sites from highly contrasting biomes across a 74° latitudinal gradient over a total of 36 site‐years. Under relatively constant conditions of light, temperature, and other environmental factors, significant diurnal NEE oscillations were observed at six sites, where daily NEE variation was between 20% and 90% of that under variable environmental conditions. These results are consistent with fluctuations driven by the circadian clock and other endogenous processes. Our results open a promising avenue of research for a more complete understanding of ecosystem fluxes that integrates from cellular to ecosystem processes.